1992
DOI: 10.1159/000462222
|View full text |Cite
|
Sign up to set email alerts
|

Red Cell and Platelet Concentrates from Blood Collected into Half- Strength Citrate Anticoagulant: Improved Maintenance of Red Cell 2,3-Diphosphoglycerate in Half-Citrate Red Cells

Abstract: This study confirms previous work suggesting equivalent in vitro properties in blood components prepared from donations collected into half-citrate preservative (HCPD) compared to components derived from donations collected into standard citrate-phosphate-dextrose (CPD) preservatives. In addition, red cell products harvested from HCPD donations showed significantly improved maintenance of pH over storage, and this was reflected in improved maintenance of intracellular 2,3-diphosphoglycerate (2,3-DPG). This eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The drawing of blood into half-strength CPD improves the maintenance of 2,3-bisphosphoglycerate during storage of red-cell concentrate [4] as well as red cells suspended in additive solutions containing citrate, phosphate and ade nine, but no chloride [5,6], Citrate in the red cell additive solution (RAS) offers possibilities to a further improvement of the storage conditions for red cells [5][6][7]. Thus, there are good reasons to lower the citrate concentration in the anti coagulant in order to avoid an increased citrate load in mas sive transfusion when plasma and red cell suspensions are transfused simultaneously.…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawing of blood into half-strength CPD improves the maintenance of 2,3-bisphosphoglycerate during storage of red-cell concentrate [4] as well as red cells suspended in additive solutions containing citrate, phosphate and ade nine, but no chloride [5,6], Citrate in the red cell additive solution (RAS) offers possibilities to a further improvement of the storage conditions for red cells [5][6][7]. Thus, there are good reasons to lower the citrate concentration in the anti coagulant in order to avoid an increased citrate load in mas sive transfusion when plasma and red cell suspensions are transfused simultaneously.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…Recent studies have shown that a half-strength citrate CPD solution (0.5CPD) improves the maintenance of eryth rocyte 2,3-bisphosphoglycerate (BPG) during storage of red cell concentrates [4], This effect is even more pro nounced when the red cells are stored in an additive solution containing citrate and no chloride [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…It gives to the blood a higher pHe as well as pHi [9,12], The latter effect prob ably explains most of the better maintenance of 2,3-DPG and P50-Since PCs are often prepared from the collected whole blood in addition to other components, it is important to know if 0.5CPD allows the preparation of platelets with similar yields or if it has any adverse effects on platelets with respect to platelet transfusions. No such effects were observed in a previous study, though [16].…”
Section: Discussionmentioning
confidence: 66%
“…Rapid cooling of the blood to 20°C is a way to counteract the loss, but even then about 60% of the original 2,3-DPG content is lost within 16 h [24], thus at a rate of about 4%h. This initial loss is less rapid when the blood is collected in 0.5CPD but great individual variations are seen [12,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation